Dampak Pengambilalihan Berita Kota oleh Manajemen Warta Kota Terhadap Persaingan Bisnis Media Cetak di Jakarta - Eman Sulaeman Nasim (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
Mass media currently plays an important role in the homeland. In addition to functioning as an agent of change and forming public opinion as well as economic and business facilities are profitable. One of the lucrative press companies to become the leading business conglomerate in Indonesia is Kompas Gramedia Group. In addition to managing the national mass media, Kompas Gramedia also manages local newspapers. Warta Kota is one of the local newspaper owned by Kompas Gramedia. In order to dominate the reader market in the capital city as well as to reach the larger advertising cake, the management of Warta Kota took over Kota Newspaper previously managed by PT Pena Mas Pewarta, and became its main competitor. The takeover of the City News newspaper is only done by purchasing the City News Newspaper. While PT Pena Mas Pewarta is not purchased. This research, want to see if what is done by Warta Karta Kota newspaper organizer is contradictory with Law No.5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, and can turn off the competitive climate and healthy competition in print mass media business in Jakarta and surrounding areas. The research was conducted using empirical law research method. Research that prioritizes field research to obtain primary data as the main data. In order to support and complement the main data, conducted by library research to obtain secondary data. Revealed the legal action conducted by the newspaper Warta Kota, in addition to avoiding the takeover of corporate responsibility of the City News Newspaper previously, as well as efforts of Kompas Gramedia to avoid acts contrary to the Law N0 5 of 1999 Article 28 (2). In addition, the Newspaper News Manager has violated Law no. 5 of 1999 Chapter IV Article 25 (1) and has violated Law no. 5 of 1999 Chapter IV Article 17 (2). What the Koran Warta Kota has done has also harmed the readers of the Kota Berita Newspaper in DKI Jakarta and its surroundings.